Impact of Peer Support towards Job Satisfaction and Organisational Relationship Behaviour among Public Service Employees - Umi Hamidaton Mohd Soffian Lee; Hanim Hj Misbah; Nor Azima Ahmad (Universiti Sains Islam Malaysia, 2025)
The Journal of Muamalat and Islamic Finance Research, Volume 22 Issue 2 Page (131–144)